The main challenges to implement a strategic plan through dynamic capabilities - Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Process Management and Benchmarking, 2022)
The globalisation, the accelerating technological evolution and the financial crisis are just some of the factors that contribute to the fast-pacing changing market conditions, requiring the companies to have the capacity to be continuously improving and adapting at the same time. Dynamic capabilities allow the organisation to transform its core and support competencies to adapt permanently and quickly to the habitat and external context, becoming the basis for the achievement of strategic objectives and sustainable growth. This research presents the results from a research which has identified that the professionals indicate one or more of three barriers as the main obstacles to implement the strategic objectives in their companies. A problem solving approach is then applied for each of the top 3 barriers, defining the barrier, analysing its impacts and their evolution over time, so as to be able to derive and recommend the solutions to overcome the barrier.